Analisis Peran Media Sosial dalam Membentuk Sikap Kritis Mahasiswa Terhadap Isu Kewarganegaraan - Hasan, Riza (Media Manajemen Pendidikan, 2024)
This study aims to analyze the role of social media in shaping the critical attitude of West Aceh State Community Academy students towards civic issues. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, participant observation, and social media content analysis. The results showed that students actively utilize various social media platforms, especially TikTok, Instagram, YouTube, and Facebook, as the main sources to access information related to citizens' rights, responsibilities, and participation. The research findings reveal that social media is not only a means of disseminating information, but also facilitates students' critical thinking process. Through interactive features on social media, students engage in discussions and share critical views on civic issues that directly affect their lives. Students no longer just passively receive information, but rather seek to analyze, evaluate and question the truth and viewpoints presented. Discussions on social media also encourage students to consider different perspectives, thus helping them to develop a more comprehensive understanding and a better critical attitude towards civic issues. The implication of this study is the importance of utilizing social media as an effective civic learning tool in higher education.